2021
DOI: 10.1002/hep4.1878
|View full text |Cite
|
Sign up to set email alerts
|

Serum Proteomics Uncovers Biomarkers of Clinical Portal Hypertension in Children With Biliary Atresia

Abstract: Children with biliary atresia (BA) often develop portal hypertension (PHT) and its complications, which are associated with high morbidity and mortality. The goal of this study was to identify serum biomarkers of PHT by using large‐scale proteomics. We applied the slow off‐rate modified aptamer scan (SOMAscan) to measure 1,305 proteins in serum samples of children with BA with and without clinical evidence of PHT in validation and discovery cohorts enrolled in the Biliary Atresia Study of Infants and Children.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…NILDA are best calibrated for chronic viral hepatitis and ALD etiologies but tend to overestimate CSPH risk in patients with obesity and NAFLD. [23] Promising, but small and nonexternally validated, studies have reported good correlation of contrast-enhanced ultrasoundderived, [73] MRI, [74] and serum biomarkers [75][76][77][78] with HVPG. However, as reviewed in the AASLD NILDA Guideline, correlations between blood-based NILDA and CSPH remains inferior to those with imagingbased NILDA.…”
Section: Do Not Use Deep Sedation (Avoid Fentanyl and Propofolmentioning
confidence: 99%
“…NILDA are best calibrated for chronic viral hepatitis and ALD etiologies but tend to overestimate CSPH risk in patients with obesity and NAFLD. [23] Promising, but small and nonexternally validated, studies have reported good correlation of contrast-enhanced ultrasoundderived, [73] MRI, [74] and serum biomarkers [75][76][77][78] with HVPG. However, as reviewed in the AASLD NILDA Guideline, correlations between blood-based NILDA and CSPH remains inferior to those with imagingbased NILDA.…”
Section: Do Not Use Deep Sedation (Avoid Fentanyl and Propofolmentioning
confidence: 99%
“…These proteins relate to angiogenesis and lymphangiogenesis, as the adaptive and compensatory mechanisms activated along the PH development [ 9 , 11 , 12 ]. Osborn et al have compared the serum proteomic profiles of children with biliary atresia and identified five protein candidates (SEMA6B, SFRP3, COMMD7, BMX, and VCAM1) in children with clinical signs of CSPH [ 13 ]. Their presumed role in the pathogenesis of PH might be illustrated by the Bone marrow kinase on chromosome X (BMX) protein that is involved in the regulation of proinflammatory cytokines secretion [ 14 ], whereas Vascular cell adhesion molecule 1 (VCAM-1) is involved in endothelial activation and angiogenesis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%